Sustainable development of agriculture: Theoretical aspects and their implications - Karol Kociszewski (Economic and Environmental Studies (E&ES), 2018)
The objective is to provide a systematization of concepts connected with sustainable development of agriculture (SDA) as the basis for indication of directions of changes in Polish agriculture. The author applied descriptive and comparative analyses based on a survey of the literature to indicate the differences between the described concepts. Both sustainable agricultural and rural development (SARD) and multifunctional rural development (MRD) could be connected with reduced agricultural production, which would bring positive and negative environmental consequences. The multifunctional agriculture cannot exist without production, so it is more favourable for SD, however it should be based on environmental requirements. Then it is close to sustainable agriculture. Considering these concepts, the author formulated and used his own definition of the SDA and its objectives. The sensitive rule of sustainability with secured critical natural capital is the proper one for agriculture in Poland. Currentl , Polish agriculture is in dual development (industrialisation and sustainable transition). For the SDA, the support for agriculture should be conditioned by compliance with basic environmental standards and by provision of public goods. It depends on properly directed and effectively implemented environmental and economic measures of the CAP.
Keywords: O13; Q15; Q18; Q57; 330; sustainable development of agriculture; sustainable agriculture and rural development; sustainable agriculture; rural development measures